Influence of smoking on salivary interleukin-8 levels in chronic periodontitis - Haween T Nanakaly; Aveen E Ismail; Daldar A Othmn (College of Dentistry/ University of Baghdad, 2020)
Background: Smoking is the major environmental risk factor that has been associated with the pathogenesis and progression of periodontal diseases. Interleukin-8 (IL-8), has been associated with the immunopathology of periodontitis. Objectives: To determine the influence of smoking on salivary Interleukin-8 level from smokers and non-smokers with periodontitis and periodontally healthy control subjects. Materials and Methods: Un-stimulated saliva samples were collected of 90 participants: 30 smokers and 30 non-smokers with chronic periodontitis, as well as 30 periodontally healthy control subjects. The clinical parameters such as the pocket depth, clinical attachment loss, plaque index, and gingival index were measured. IL-8 level in the saliva was measured by Enzyme Linked Immunosorbent Assay (ELISA) kit. Results: It was found that the mean value of salivary IL-8 levels was significantly higher in smokers (461.76 ± 329.66 ng/L) than in non-smokers periodontitis (257.83 ± 247.19 ng/L) and the controls (96.55 ± 62.35 ng/L) (p < 0.001). Moreover, salivary IL-8 levels were significantly higher in smokers compared with non-smokers periodontitis (p< 0.001). Conclusion: Smoking subjects showed increased level of salivary IL-8 and a worse periodontal condition than non-smoking subjects. Our results suggest that smoking alters an immune response which may contribute to an increased susceptibility to periodontal disease among smokers Keywords: Smoking; Chronic periodontitis; Saliva; Interleukine-8